Biodiesel fuels from palm oil, palm oil methylester and ester-diesel blends - C.M.A.O. Martins; V.O. Ajibola; V.I.E. Ajiwe (Bulletin of the Chemical Society of Ethiopia, 2003)
Because of increasing cost and environmental pollution effects of fossil fuels, palm oil, its methylester and ester-diesel blends were analyzed comparatively with diesel for their fuel properties that will make them serve as alternatives to diesel in diesel engines. Equally, the samples were comparatively analyzed for their trace metal composition in relation to corrosion. Also the bond structure/stability of the samples in relation to diesel were monitored with a Fourier transform infrared spectrometer. Results confirmed that most methylester blends with diesel fell within the grade 2D while the oil, methylester and 90:10 blend fell into 4D grade diesel fuels. From bond structure/stability comparison, all the samples were stable at 28 oC and had similarity in structure with diesel. All samples are commercializable. The trace metal composition of most samples was below that of the diesel with exception of Mn, Pb and Zn. The total acid numbers of all samples were below that of diesel and would not cause corrosion. It is recommended that processing of these samples should be done to conserve fossil fuel and as alternative diesel fuels in diesel engines.